2012
DOI: 10.4049/jimmunol.1101018
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Hypertrophy following Leishmania major Infection Is Dependent on TLR9

Abstract: Control of the protozoan parasite, Leishmania major, is dependent upon establishing a robust T cell response. An early event in the development of an effective T cell response is the expansion (or hypertrophy) of the lymph node draining the site of infection, although the mechanisms involved in this response are not completely understood. Here we show that lymph node hypertrophy following L. major infection in mice is associated with increased recruitment of lymphocytes to the lymph node from the blood, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
(70 reference statements)
2
41
1
1
Order By: Relevance
“…DC activation by different Leishmania species (L. major and L. infantum) was reported to be TLR9 dependent. L. braziliensis was also shown to induce IL-12 release by DCs in a TLR9-dependent manner (23,25,30,31). However, L. braziliensis strains can harbor Leishmania RNA virus (LRV1) (45), and the presence of LRV1 could influence the immune response, as was shown in L. guyanensis infection (37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DC activation by different Leishmania species (L. major and L. infantum) was reported to be TLR9 dependent. L. braziliensis was also shown to induce IL-12 release by DCs in a TLR9-dependent manner (23,25,30,31). However, L. braziliensis strains can harbor Leishmania RNA virus (LRV1) (45), and the presence of LRV1 could influence the immune response, as was shown in L. guyanensis infection (37).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, L. braziliensis infection has been associated with the presence of enlarged dLNs that harbor parasites, and this lymphadenopathy occurs prior to lesion development (46,47). The increased levels of IFN-␥ at the site of infection and in the dLNs suggested that cell migration to the dLNs is normal in TLR9 Ϫ/Ϫ mice infected with L. braziliensis, which is in contrast to findings for L. major-infected TLR9 Ϫ/Ϫ mice, which exhibit dLN hypotrophy (31). We therefore determined if the increased susceptibility in L. braziliensis-inoculated TLR9 Ϫ/Ϫ mice was associated with altered dLN expansion.…”
Section: Ifn-␥ Production Is Higher In Dln Cells From Tlr9mentioning
confidence: 88%
See 2 more Smart Citations
“…Overall, during the virus infection, TLR2/9 stimulation can mediate NK recruitment directly via the production of chemokines, as well as enhance the CD69 expression and cytokine secretion. Just during the cutaneous leishmaniasis challenge, NK cells represent an important source for early IFN-, and TLR9 is essential for the induction of NK cell-related IFN- secretion and cytotoxicity during the innate phase of Leishmania (L.) major infection, because lymph node (LN) NK cells from TLR9 -/-mice acquired no cytolytic activity after stimulation with L. major [66]. Further study showed that activation of DCs via TLR9 was essential for the induction of hypertrophy in leishmaniasis, due to the crosstalk between NK cells and DCs [67].…”
Section: Tlr Signaling On Nk Cell Activationmentioning
confidence: 99%